ESTIMATION OF TOTAL PHENOLIC AND FLAVONOID CONTENT OF POLYHERBAL FORMULATION DASHANG LEPA - Ashish, Soni; Gupta, S J; Amit, Kumar; Tripathi, Y B (International Journal of Ayurveda and Pharma Research, 2015)
Background: Indian system of medicine mainly based on polyherbal compound to treat various types of diseases. Dashang lepa is one of the prestigious formulation of ten indigenous drugs which are having predominantly anti-inflammatory properties and clinically used in inflammatory swelling like boil, furunculosis, cellulitis, erysipelas etc. As several reports are on various individual phytochemical, phenolic and flavonoid content but none is having study of polyherbal compound Dashang lepa. Objectives: Total phenolic and total flavonoid content were studied of alcoholic extract of Dashang lepa. Method: Methanolic extraction was done by hot percolation method through soxhlet apparatus. Phenolic content was estimated using Follin ciocalteau reagent, flavonoid using aluminum chloride (2%) reagent as quercetin equivalent. Results: Estimation of total phenolic and total flavonoid content showed that Dashang lepa extract was having phenolic content (15.8±1.14) ug Gallic acid equivalents (GAE) and flavonoid content (22.4±2.54) in ug of quercetin equivalents (QE).